HUBUNGAN ANTARA KREATIVITAS DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA STKIP PARIS BARANTAI KOTABARU - Abdul Rahman (STKIP Paris Barantai, 2014)
ABSTRACTStudents are still difficult or slow in grasping math, it's effect on student achievement, some of the factors that affect the high and low student achievement, including internal factors and external factors. Creativity and learning styles are internal factors contained in students who can support and can also inhibit the mathematics achievement. The purpose of this study to determine the relationship between creativity and learning styles on student achievement STKIP Paris Barantai Kotabaru. The method used in this research is descriptive method. Data collection techniques used were questionnaires and documentation, for data analysis used descriptive statistics and inferential statistics which include tests of normality, linearity test, Pearson product moment correlation and multiple correlation. The results obtained based on the analysis of data and discussion indicate that (1) the relationship of creativity on student achievement STKIP Paris Barantai Kotabaru have a fairly high degree of correlation with a correlation value of 0,507; (2) the relationship of learning styles on student achievement STKIP Paris Barantai Kotabaru have a high degree of correlation with a correlation value of 0,761; (3) the relationship between creativity and learning styles on student achievement STKIP Paris Barantai Kotabaru has a significant relationship with the value of Fhitung >Ftabel .Â Key words: Creativity, learning style, academic achievemen